2015
DOI: 10.1097/mcg.0000000000000198
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Stenting With Sutures

Abstract: Anchoring of the upper flare of the FCSEMS with endoscopic sutures is technically feasible and significantly reduces stent migration rate when compared with no suturing, and is a safe procedure with very low AEs rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…However, the use of cSEMS has demonstrated high rates of migration that may occur early in the period after stent placement, which may ultimately compromise long-term clinical success. Endoscopic suturing of cSEMS to tissue has been a recent advance that has mitigated this issue of migration[ 8 ], but this procedure is expensive and can be technically challenging[ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of cSEMS has demonstrated high rates of migration that may occur early in the period after stent placement, which may ultimately compromise long-term clinical success. Endoscopic suturing of cSEMS to tissue has been a recent advance that has mitigated this issue of migration[ 8 ], but this procedure is expensive and can be technically challenging[ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a recently published cohort of patients with prior FCSEMS migration, Irani et al [10] showed an 85% reduction in stent migration when an OTS clipping device (OTSC; Ovesco, Tubingen, Germany) was used to anchor the FCSEMS. As mentioned previously, published data suggest a reduced rate of stent migration among patients that underwent suture fixation of esophageal FCSEMS compared to non-anchored controls (11.7 vs. 55%) [2]. OTS clipping devices and endoscopic suturing both appear to be promising techniques for reducing FCSEMS migration, but come with an increase in procedural costs (~$300–$800) which must be considered.…”
Section: Discussionmentioning
confidence: 96%
“…Esophageal FCSEMS (1) provide resistance to tissue ingrowth in malignant or benign strictures, (2) provide a luminal seal over perforations, leaks, and fistulae, and (3) are generally retrievable without difficulty. Historically, the major limitation of FCSEMS placement has been stent migration, occurring in up to 30–55% of cases [24]. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Through-the-endoscope clips are of limited value[86,117,118] and limited experience with the new endoscopic suturing devices to anchor the stents shows variable results[119,120]. …”
Section: Anastomotic Leaks and Fistulasmentioning
confidence: 99%